Australia from $50 a day - Llewellyn, Marc (Hungry Minds, 2002)
From the panhandle to Key West, vacationers can use this full-color guide to explore Florida at their own pace. Maps and stunning photographs tempt drivers to choose from the many driving tour options, including scenic detours and spectacular views